Avelumab versus standard second line treatment chemotherapy in metastatic colorectal cancer patients with microsatellite instability: The SAMCO-PRODIGE 54 randomised phase II trial. Issue 3 (March 2021) - Taïeb, Julien; André, Thierry; El Hajbi, Farid; Barbier, Emilie; Toullec, Clémence; Kim, Stefano; Bouche, Olivier; Di Fiore, Frederic; Chauvenet, Marion; Perrier, Hervé; Evesque, Ludovic; Laurent-Puig, Pierre; et al.
Abstract: Immune checkpoint inhibitors have failed in treating metastatic colorectal cancer (mCRC) patients except those with dMMR/MSI tumors. However, until very recently we had only non-comparative promising data in this population with anti-programmed cell death 1/ programmed cell death ligand 1 (PD1/PD-L1) antibodies alone or combined with anti- cytotoxic T-lymphocyte-associated protein 4 (CTLA4) antibodies. This comparative phase II trial (NCT 03186326), conducted in more than 100 centers in France, will include dMMR/MSI mCRC patients with progression after a first-line treatment with chemotherapy ± targeted therapies, to evaluate efficacy and safety of the anti-PDL1 Avelumab versus a standard second-line treatment. Main inclusion criteria were patients aged 18 to 75 years, ECOG performance status ≤2, dMMR/MSI mCRC and failure of a standard first-line regimen. Patient will be randomised to receive Avelumab 10 mg/kg versus standard second-line doublet chemotherapy plus a targeted agent according to tumor RAS status. Patients will be followed for 4 years. A gain of 5 months in median PFS is expected in favour of the Avelumab arm (12 vs 7 months; HR=0.58). Secondary endpoints include objective response rate, overall survival, quality of life and toxicity. In addition, circulating tumour DNA and microbiota will be explored to test their potential prognostic and predictive values. The study was opened in March 2018.